The influence of competition on quality of hospital treatment from physician behavior perspective (theoretical model verification with case presentation from Vinnitsa, Ukraine) - Yaremyna, Iryna; Ocheredko, Oleksandr (ScienceRise: Medical Science, 2017)
The aim of the study was to check theoretical proposition of elaborated by our research team theoretical model [1], i.e. physician’s emphasis to clinical hours instead of nonclinical within the relenting competition may interfere quality. Methods. We collected the data by stratified panel design between departments of the city hospital No. 1, starting in 2008 with randomized inclusion. Thereafter, to sustain statistical significance we got on with total coverage up to January 31, 2012. Thus, we considered 2680 admission cases totally. Length of period between subsequent admissions (LBA) considered as the measure of treatment quality. We proceeded the data with competing risk modelling having in mind 2 types of subsequent admissions, that is the same cause of next admission and the different one. Results. Lengthier hospital staying provided within the competition indeed safeguarded quality (increase in LBA) in case of the same cause admission, Z-test scored 1,957 with р=0,025. The effect was not significant for the next admissions due to different cause with Z scoring 0,128, р2=0,449. Still effect is positive (q=1,014). We think it’s important for validation of deduction, so far as better quality reduces patient’s frailty for both types of admissions. Conclusion. We empirically checked the hypothesis stemming from theoretical model of physician’s behavior on part of possible impairment of quality under market monopoly. The theoretical model unveiled one of the key issue – physician’s emphasis toward clinical hours instead of nonclinical that necessarily interferes the quality. Empirical verification based on instances of patient overloads in the process of health reform in the city of Vinnitsa. Findings supported hypothesis, i.e. physician’s emphasis toward clinical hours instead of nonclinical within relenting competition indeed impinged on quality of treatment indicted by LBA shortening. We clarified the LBA increase with lengthier hospital staying envisaged under competition. Z-test scored 1,957 with р=0,025) in case of the same cause admission, and it was insignificant for next admissions due to different cause with the same direction of the effect.